Pan-Cancer Analyses Reveal Oncogenic and Immunological Role of PLOD2 - Xu, Qiqi; Kong, Na; Zhao, Yiguo; Wu, Quan; Wang, Xin; Xun, Xiaodong; Gao, Pengji (Frontiers in Genetics, 2022)
Previous studies have shown the diagnostic and prognostic value of the PLOD2 gene in various types of malignancies. However, the value of PLOD2 in pan-cancer remains less clear. The present study aimed to profoundly elucidate the differential expression of PLOD2 gene in 33 of pan-cancers and focused on the value with respect to tumor immunity and prognosis. First, we integrated GTEx, TCGA and CCLE databases to analyze the expression of PLOD2, and found that it was expressed differently in normal tissues and significantly highly expressed in most tumors. Second, our analysis revealed that PLOD2 expression was significantly correlated with the prognosis of a variety of tumors, with most tumors showing a negative correlation between high PLOD2 expression and prognosis. For gastric cancer, the median overall survival time was significantly higher in the PLOD2 low expression group (HR 0.616 [95%CI 0.442-0.858], P=0.004). Third, for tumor immunity, PLOD2 was significantly associated with tumor infiltration, including immune infiltrating cells; immune checkpoint expression; immune microenvironment scores (immune score, stromal score and estimate scores); immunotherapy-related scores (tumor mutational burden, microsatellite instability, tumor neoantigen burden); expression of DNA repair genes (MMRs) and methyltransferase; and enrichment analyses identified PLOD2-associated terms and pathways. Lastly, twenty pairs of gastric cancer and adjacent immunohistochemistry showed that PLOD2 was significantly overexpressed in gastric cancer (P<0.001). Collectively, PLOD2 played a significant role in tumorigenesis and maybe serve as a potential biomarker for diagnosis and prognosis in cancers.